An initial study into augmented inward looking exploration and navigation in CAVE-like IPT systems - Aspin, Rob (2008 IEEE Virtual Reality Conference, 2008)
This research presents and evaluates a CAVE-like IPT system in which a tracked display and interaction device (TDID), based on a tablet PC, is used to display an augmented viewing system for detailed examination of a close focused objects. This maintains wider context, displayed on the IPT display environment, thereby enabling effective wayfinding and navigation, while still enabling detailed examination of the region of interest on a position sensitive high-resolution display (TDID). Evaluation against an un- augmented CAVE-like IPT system, demonstrates the effectiveness of this approach in enabling users to both explore around the model effectively resolve fine detail.